1984
DOI: 10.1080/15287398409530520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simultaneous prenatal exposure to ochratoxin a and citr1nin in the rat

Abstract: Ochratoxin A (OA) and citrinin (CT) are food-borne mycotoxins produced by several fungal species of the genera Aspergillus and Penicillium. Both are teratogenic in the rat. To determine the prenatal effects of simultaneous exposure to these toxins, pregnant Sprague-Dawley rats were injected either with a single individual subthreshold teratogenic dose of OA (1 mg/kg) or CT (30 mg/kg) or with both toxins. Toxins were dissolved in 5% sodium bicarbonate and administered subcutaneously on one of gestation d 5, 6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 11 publications
2
20
1
1
Order By: Relevance
“…The litter data showed 12.50% resorptions and 13.39% post implantation losses in the CIT group which was in agreement with the earlier findings in rats (Reddy et al, 1982;Mayura et al, 1984). These workers reported resorptions at a dose rate of 36 mg kg −1 b.w.…”
Section: Discussionsupporting
confidence: 92%
“…The litter data showed 12.50% resorptions and 13.39% post implantation losses in the CIT group which was in agreement with the earlier findings in rats (Reddy et al, 1982;Mayura et al, 1984). These workers reported resorptions at a dose rate of 36 mg kg −1 b.w.…”
Section: Discussionsupporting
confidence: 92%
“…In our combinatorial toxicity study we reduced the concentration to similar percentile values of the respective individual IC 50 values and obtained best results at 20% of the respective IC 50 values. Quite a few previous studies also reported synergistic/additive/antagonistic interaction between OTA and CTN in different models and for different end points (Summarized by F€ ollmann et al, 2014;Also, Siraj et al, 1981;Vesela et al, 1983;Mayura et al, 1984;Manning et al, 1985;Brown et al, 1986;Аnninou et al, 2014). But in nature mycotoxins can co-occur in any ratio (Bosulimi et al, 2008a), and the effect of mixtures is often dependent on the concentrations wherein an effect can change from additive to synergistic with increasing concentrations (F€ ollmann et al, 2014).…”
Section: Discussionmentioning
confidence: 89%
“…to cause multiple teratogenic effects in developing rat embryos without coincident deleterious effects in the dams. 188 Thus, it appears that the teratogenic effects mediated by OTA are caused by a direct action of the parent compound on the developing fetus. The observations of Arora and coworkers 189 seem to corroborate these observations, as simultaneous administration of diethylstilbestrol and zearalenone, both of which have been shown to reduce transplacental blood flow, resulted in an overall reduction or absence of abnormal fetuses in rats exposed to OTA.…”
Section: Ota Causes Specific Developmental Defectsmentioning
confidence: 99%